A Methodological Strategy for the Family Health Course in General Internal Medicine Residency - Mabel Rocha Vázquez; María Aurelia San Juan Bosch (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: the continuous improvement of the educational process is one of the permanent challenges of medical education in Cuba. When dealing particularly with family medicine it must be ensured that physicians are always getting a better clinical approach to the management of families, since this is one of the key areas that have been identified as problematic in professional practices. Objective: to design a methodological strategy for the improvement of educational activities in the Family Health Course of the General Internal Medicine Residency. Method: a development research, conducted at the University of Medical Sciences of Cienfuegos, from November 2005 to January 2007 is presented. Document analysis and validation by expert criteria were also implemented. Results: for each of the four themes that make up this course, the following aspects are stated: teaching organization, length, contents, activity objectives, methodological guidelines to implement these activities, assessment proposals for some of them and some literature. Conclusions: the design of educational activities, with emphasis on actual or simulated medical practice, could help improving the quality of the teaching process. In addition, following the logical structure of activities, teachers can develop similar proposals to address other health problems according to the different learning needs.